Video streaming industry: how can streaming video companies boost customer re-purchase intention within Portugal - Santos, Rúben Alexandre (2024)
The burgeoning expansion of video streaming has profoundly disrupted traditional television. A compelling topic emerges as the industry undergoes dynamic transformations, and understanding customer repurchase intention is vital for sustained business success. Focused on Portugal, the research investigates strategies for enhancing repurchase intention among five prominent brands – Netflix, HBO Max, Disney +, Amazon Prime Video, and Apple TV +. To perform this study, some preliminary interviews were conducted, followed by two analytical approaches, conjoint and perceptual maps analysis, delineating preferences, and perceptions regarding the aforementioned brands. Additionally, it emphasized attributes such as shows virality, with potential dispersion in preferences mitigated through strategic technological innovation.